Composite Nanocrystalline/Amorphous Thin Films for Particle Detector Applications. Issue 1770 (2015) - Razieli, Zvie; Rusack, Roger; Kakalios, James
ABSTRACT: Thin films of amorphous silicon with nanocrystalline silicon inclusions are fabricated using a dual plasma PECVD co-deposition system. Raman spectroscopy and X-ray diffraction confirmed the crystallinity of the embedded nanocrystals as well as their diameter, which is varied from 4.3 nm to 17.5 nm. The dark conductivity of the films is highly dependent on the crystal fraction, with a maximum room temperature conductivity found for a crystal concentration of 5.5%, well below the percolation threshold. Proton irradiation at energies of 217 MeV with a total fluence of 5 x10 12 protons/cm 2 caused no significant radiation damage. The enhancement of the conductivity, along with the absence of radiation damage suggests this material may be a candidate for use in the next generation of particle detectors in the Compact Muon Solenoid in the Large Hadron Collider at CERN.